Factors driving frequent attendance at emergency departments for patients with head and neck cancer. Issue 11 (18th August 2019) - Tan, Aidan L.; Iyer, Narayanan Gopalakrishna; Putri, Natascha; Nadkarni, Nivedita; Skanthakumar, Thakshayeni; Wong, Ting Hway; Tay, Gerald Ci An
Abstract: Background: Patients with head and neck cancer have a higher risk of emergency department (ED) frequent attender (FA). We hypothesized that FAs present with issues different from non‐FAs. Methods: A retrospective cohort study was conducted on Singapore residents with head and neck cancers using de‐identified registry merged with electronic medical record data. A competing risk regression analysis was performed to identify factors associated with FA. Aggregated primary diagnoses were compared for patients with and without FA risk factors. Results: Thirteen percent of patients with head and neck cancer were FAs. FA risk factors were Charlson comorbidity index (3+), and socioeconomic status (SES). FAs had a higher proportion of respiratory infections. The spectrum of diagnosis was similar for patients with low and high SES. Current smokers had a greater proportion of respiratory complaints, relative to never smokers. Conclusion: Patients with greater comorbidity scores or higher SES were more likely to be FA. FAs were more likely to present with respiratory complaints, likely related to cancer treatment, or smoking status.